Applying old tools to new challenges - Marie Laur (Oñati Socio-Legal Series)
As states of emergency are becoming increasingly pervasive, courts can no longer rely on deferential approaches based on the assumption that emergencies are exceptional and temporary. This article investigates two mechanisms of judicial review in the case law of the ECtHR, French Constitutional Council and Council of State. The first mechanism is the review of the existence of the circumstances justifying the exceptional powers and restrictions on human rights. The second is the misuse of power or détournement de pouvoir doctrine. The article argues that both these elements of judicial review are under exploited while presenting the advantage of being readily available – therefore requiring no judicial creation – and offering strong bases to curb abuses of emergency powers. Examined at two different levels, national and regional, these two lines of reasoning, if deployed appropriately, might inspire further jurisdictions faced with similar emergency challenges.